Prof. Dr. Martin Doevenspeck and Dr. Victor Iwuoha on mobilization policies in West Africa - Doevenspeck, Martin; Iwuoha, Victor (Cluster Conversations, 2024)
In this latest episode of our podcast, fellow Dr. Victor Iwuoha talks with his host Prof. Dr. Doevenspeck about his latest research on Biometric ID Policies, Gendered Dynamics, and Political Mobilization of Migrants in West Africa. The senior lecturer at the Department of Political Science at the University of Nigeria scrutinizes how the intrusion of biometric ID technologies into the conduct of cross-border management has revealed radically in political mobilization of migrants across West African borderlands especially in Nigeria.